Enuresis in children of primary school age and factors affecting enuresis - Göksu, Mehmet; Özel, Ş. Kerem; Koç, Mustafa; Kazez, Ahmet (Logos Medical Publishing, 2020)
Objective: With this study, it was aimed to reveal the frequency of monosymptomatic enuresis (MSE) and factors affecting MSE in school children aged 7-12 years in Elazığ city. Method: In our study, a total of 1888 students, including 945 boys and 943 girls aged between 7-12, were included with the simple random sampling method. In our study, a questionnaire containing factors that might affect enuresis was used. Detailed histories of all cases were taken, physical examinations and laboratory examinations were performed. The findings were evaluated by the chi-square test. Results: MSE was detected in 352 (18.6%) of 1888 students. The frequency of MSE in boys was 20.8% (n=197) and 16.4% (n=155) in girls (P=0.044). The rate of MSE was higher in children with a family history of epilepsy (6.8%) compared to those without (3.4%) (P=0.013). The monthly income level of families of enuretic children is below the minimum wage in 53.1% (n=186), between the minimum wage and twice its amount in 34.9% (n=122), and more than twice the minimum wage in 12.0% (n=42) of the families. (P=0.027). MSE was present in 18.8% of circumcised and 27.2% of non-circumcised children. Cardiac murmur was found in 4.3% of enuretic and 0.3% of nonenuretic patients (P=0.001). Inguinal hernia enuresis was detected in 0.6%, of enuretic, and in 0.2% (P=0.001) of nonenuretic, patients. While undescended testicular was found in 1.7% of enuretic, and in 0.1% of nonenuretic patients (P=0.001). Sacral hair growth, dermal sinus, and hyperpigmentation was encountered in 11.7% of enuretic children (P=0.001). Conclusion: It has been understood that the incidence of MSE is higher in Elazig Province, according to the literature. While the frequency of enuresis decreased in circumcised patients, an inverse relationship was detected between income level and enuresis. It was determined that enuresis decreased school success. In addition, enuresis is more common with pathologies such as family history of epilepsy, cardiac murmur, inguinal hernia, undescended testicle, sacral hair growth, dermal sinus and hyperpigmentation. © Turkey Association of Pediatric Surgery.
İlkokul çağındaki çocuklarda enürezis ve enürezise etkisi olan faktörler
Keywords: additional pathologies; etiology; frequency; Monosymptomatic enuresis